Interleukin-6 Modulates Colonic Transepithelial Ion Transport in the Stress-Sensitive Wistar Kyoto Rat - O'Malley, Dervla; Dinan, Timothy; Cryan, John F. (Frontiers in Pharmacology, 2012)
Immunological challenge stimulates secretion of the pro-inflammatory cytokine interleukin (IL)-6, resulting in variety of biological responses. In the gastrointestinal (GI) tract, IL-6 modulates the excitability of sub-mucosal neurons and stimulates secretion into the colonic lumen. When considered in the context of the functional bowel disorder, irritable bowel syndrome (IBS), where plasma levels of IL-6 are elevated, this may reflect an important molecular mechanism contributing to symptom flares, particularly in the diarrhoea-predominant phenotype. In these studies, colonic ion transport, an indicator of absorption and secretion, was assessed in the stress-sensitive Wistar Kyoto (WKY) rat model of IBS. Mucosa-submucosal colonic preparations from WKY and control Sprague Dawley (SD) rats were mounted in Ussing chambers and the basal short circuit current (ISC) was electrophysiologically recorded and compared between the strains. Exposure to IL-6 (1nM) stimulated a secretory current of greater amplitude in WKY as compared to SD samples. Furthermore, the observed IL-6-mediated potentiation of secretory currents evoked by veratridine and capsaicin in SD rats was blunted in WKY rats. Exposure to IL-6 also stimulated an increase in trans-epithelial resistance in both SD and WKY colonic tissue. These studies demonstrate that the neuroexcitatory effects of IL-6 on submucosal plexi have functional consequences with alterations in both colonic secretory activity and permeability. The IL-6-induced increase in colonic secretory activity appears to neurally-mediated. Thus, local increases in IL-6 levels and subsequent activation of enteric neurons may underlie alterations in absorpto-secretory function in the WKY model of IBS.